Chemical composition and physical properties of the fiber fraction of different production batches of Plukenetia volubilis L. cake - Hernández Lemus, Susan K.; Martínez-Pérez, Madeleidy; García Hernández, Yaneisy; Herrera Galindo, Hilda; Scull Rodríguez, Idania; Villanueva Domínguez, Mabel (Cuban Journal of Agricultural Science, 2025)
To determine the chemical composition (dry matter, crude protein, ash, neutral detergent fiber, acid detergent fiber, cellulose, lignin and hemicellulose), and physical properties (solubility, water adsorption capacity and volume) of three batches of Plukenetia volubilis L. (Sacha inchi) cake, as well as its mineral profile (Ca, P, Mg, K, Na) and secondary metabolites, a simple classification design was applied and differences were analyzed using ANOVA and Duncan test (p<0.05) with the use of INFOSTAT. Results showed significant differences (p<0.05) in NDF (batch three: 25.82 % vs. batches one and two: 28.11-29.90 %), DM, ADF, and cellulose, which did not vary among all batches. There were no differences (p>0.05) in CP, lignin, hemicellulose, nor in the physical properties. Batch three showed a higher content of macrominerals (except phosphorus) compared to batch two, while batch one showed intermediate values: Ca (0.19 %), P (0.79 %), Mg (0.12 %), K (0.24 %) and Na (0.44 %). Saponins and α-amino groups were identified qualitatively, being abundant in all batches. It is concluded that the chemical composition of Sacha inchi cake varies among batches, except for protein, lignin, and physical properties. Batch three stood out for its lower content of NDF and higher mineral concentration, suggesting its potential preference for nutritional applications.